Implementation of the Principle of Precaution in the Creation of Authentic PPAT Deeds to Prevent Fraud and Misuse of Certificates in Land Sale and Purchase Transactions in Tegal City - Mahmudah, Santriany; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The sale and purchase of land in Indonesia requires strong legal certainty and preventive safeguards due to the high economic value and the vulnerability of such transactions to fraud and certificate misuse. As a public official authorized to draft authentic deeds, the Land Deed Official (PPAT) holds a central role in ensuring that every land transaction is conducted transparently, legally, and in accordance with established procedures. This study analyzes the implementation of the principle of prudence by PPATs in Tegal City as a preventive mechanism against fraud and a means of providing legal protection for sellers, buyers, and third parties. Employing an empirical legal research method combined with a quantitative approach, data were obtained through field observations, in-depth interviews with PPATs, supporting government agencies, and transaction participants, supplemented by statutory and literature review. The findings show that PPATs in Tegal City consistently apply prudential measures such as verifying certificate authenticity, examining identity documents through official population data, conducting field inspections, and ensuring the physical presence and genuine intent (wilsverklaring) of the parties during deed execution. These practices not only prevent fraudulent acts—including certificate forgery, unauthorized land sales, and misuse of powers of attorney—but also provide substantive legal protection by ensuring that the deed accurately reflects the true legal will and factual circumstances of the transaction. The study concludes that the principle of prudence constitutes a core element of professional responsibility within the PPAT's mandate, functioning as both a preventive and repressive legal protection instrument, thereby strengthening public trust and enhancing the integrity of Indonesia's land administration system.